New social & collaborative interactive TV program formats - Bachmayer, S.; Lugmayr, Artur; Kotsis, G. (2009)
TV goes rapidly digital, and more and more content formats are entering the consumer market. Currently there exist many approaches towards the development of more social, more collaborative, and interactive TV formats and systems. Within the scope of this paper we present latest case studies and provide a simple categorization according narration character, content types, and interactivity types of program formats. We also present systems supporting social and collaborative functionalities. The paper rounds up with a discussion sections, where an evaluation of the discussed projects can be found. Copyright 2009 ACM.